Experiences and needs of people with haematological cancers during the COVID‐19 pandemic: A qualitative study. Issue 3 (9th September 2021) - Zomerdijk, Nienke; Jongenelis, Michelle; Yuen, Eva; Turner, Jane; Huntley, Kathryn; Smith, Andrew; McIntosh, Megan; Short, Camille E.
Abstract: Objective: Haematological cancer patients are particularly vulnerable to the effects of COVID‐19. In addition to being immunocompromised, pandemic‐related travel restrictions have impacted access to treatments and overseas stem cell donations for patients requiring transplantation. Given this vulnerability, people with haematological cancers are at risk of experiencing heightened distress during the pandemic. This study aimed to explore haematological cancer patients' experiences and needs. Methods: Twenty‐four Australian haematological cancer patients completed semi‐structured interviews exploring their concerns and worries during the pandemic, impact of pandemic on management of disease, access to information and support, lifestyle changes, and attitudes towards emerging models of healthcare during the pandemic. Interview transcripts were thematically analysed. Results: Four themes reflecting the experiences of haematological cancer patients during the pandemic were identified: 'Fears about contracting COVID‐19' (behaviour changes to protect health, impact on daily routine and habits, annoyance at dismissive attitude of others toward COVID‐19); 'Reduced sense of connection and support' (reduced social support and access to external support services); 'New challenges' (increased financial hardship, worsened health), and; 'Underlying system and communication issues' (access to trusted information, satisfaction/dissatisfaction with care, navigating telehealth). Participants expressed a need for improved access to support services and trusted information. Conclusions: The findings emphasise the additional challenges experienced by haematological cancer patients during the COVID‐19 pandemic and their impact on daily life. Results point to the importance of validation of increased distress during periods of uncertainty; reinforcing recommendations about high‐quality sources of information; and facilitating access to support services when face‐to‐face care is limited.